EFEKTIVITAS PELAKSANAAN KEGIATAN POSYANDU HARUM SARI RT.01/ RW.05 KELURAHAN TANGKERANG SELATAN KECAMATAN BUKIT RAYA PEKANBARU - Nainggolan, Nita Astriani Nainggolan Astriani; Jas, Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstarct: This research aims to know The effectiveness of Posyandu Harum Sari Application RT.01/RW.05. Tangkerang Selatan District, Bukit Raya Pekanbaru. This research use naturalistic description by qualitative approach that purpose to give description systematically about the situation that being the objective of the research The effectiveness of Posyandu Harum Sari Application RT.01/RW.05 Tangkerang Selatan District, Bukit Raya Pekanbaru. The data collecting technique is observation, interview,  and documentation. The data is achieved from the subject of the research includes two basic participants, controll participants and observed participants. The research findings of this research is Harum Sari Posyandu not be succes fully in achieving the activity application. So, it is still be done an effor to increase the participation and society in application even increase the service. The human resource in Harum Sari Posyandu encourages activity application as device, infrastructure, cadre, and donation. Device and infrastructure is table and chairs, children scales, and adult scales, bedroom, medicines, children foods. Meanwhile, the donation of the application is achieved from society, and RT. The acceptance and society cadre beliefs about Posyandu is good. It can be seen from their spirit in giving the posyandu service. Furthermore, the fifth participants states that the visitor accept and belief that the posyandu is good and proper. The cadre satisfaction in giving health service in Posyandu is good enough. Then the visitor satisfaction in accepting the health service at Posyandu. Key Words: Effectiveness, Posyandu Application.